PsycEXTRA Dataset 2013
DOI: 10.1037/e562792013-011
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Analysis of the Workplace Forgiveness Scale

Abstract: Though there are measures of forgiveness published in the behavioural science literature, very few scales are available to measure forgiveness in workplace relationships. The Workplace Forgiveness Scale aimed to measure forgiveness of a specific offense. Data from 348 professional nurses in Thailand were subjected to an exploratory factor analysis (EFA) and the psychometric properties of the scale were examined. Results from EFA suggested retaining four underlying factors of the forgiveness construct: Overcomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Referring to the past studies, the external validity was measured with convergent validity (correlation with similar measure) and discriminant validity (correlation with dissimilar measure) of the complete scale (Boonyriat et al , 2013; Heun et al , 1999; Olsen et al , 2003).…”
Section: Studymentioning
confidence: 99%
“…Referring to the past studies, the external validity was measured with convergent validity (correlation with similar measure) and discriminant validity (correlation with dissimilar measure) of the complete scale (Boonyriat et al , 2013; Heun et al , 1999; Olsen et al , 2003).…”
Section: Studymentioning
confidence: 99%
“…In turn, it has a significant impact on overall relationship satisfaction (Braithwaite et al, 2012). Moreover, employing forgiveness as a problem-solving approach can effectively mitigate feelings of anger, the desire for revenge, and negative judgments toward the person who offended (Boonyarit et al, 2013). The second element is self-efficacy, which is significantly furnish to psychological well-being (Rathi & Rastogi, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…At the intrapersonal level, extant studies focused mostly on social cognitive determinants, such as rumination and empathy, attributions, and transgression severity. Consistent with research in close relationships (McCullough et al, 2007), rumination has been shown to be negatively associated with forgiveness in work relationships, such that repetitive thinking about hurtful offenses generally makes it harder to forgive an offending coworker (Boonyarit et al, 2013;Tarraf et al, 2019). Empathy, including both the cognitive (i.e., understanding others' internal states) and affective dimension (i.e., feeling congruent emotions with others) (e.g., Clark et al, 2019), has also been positively associated with forgiveness in the workplace (Ran et al, 2021).…”
Section: What Is Already Known About Forgiveness In Work Relationships?mentioning
confidence: 57%